2017
DOI: 10.22159/ajpcr.2017.v10i5.16078
|View full text |Cite
|
Sign up to set email alerts
|

Co-Morbidity of Cardiovascular Diseases and Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic disease related to swelling of joints which lead to restriction in movement due to pain and deformity mainly in feet, ankle, wrist, and fingers. It is an autoimmune disease, and the manifestations caused due to its occurrence are not clearly understood. In today's time, it has been observed that comorbid conditions account for most of the deaths as they influence the outcome of RA and limit therapeutic options. The most common comorbid conditions which are diagnosed in RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…There is more risk of stroke and myocardial infraction about 2-fold increase in the patients of RA which are suffering from about 10 y or more. It has been concluded that the patients of RA show more risk of having heart disease which can lead to increase mortality rates [26].…”
Section: Demonstrations Related With Rheumatoid Arthritismentioning
confidence: 99%
“…There is more risk of stroke and myocardial infraction about 2-fold increase in the patients of RA which are suffering from about 10 y or more. It has been concluded that the patients of RA show more risk of having heart disease which can lead to increase mortality rates [26].…”
Section: Demonstrations Related With Rheumatoid Arthritismentioning
confidence: 99%